2020
DOI: 10.21203/rs.3.rs-30401/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In-silico analysis of potential interaction of drugs and the SARS-CoV-2 spike protein

Abstract: The world is suffering its deadly pandemic in decades from Corona virus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Till the end of April, 2020, the death toll rose to more than 2 lacs worldwide (224 301, on May 1st), affecting 215 countries (source: WHO). Since the invention of a new drug or vaccine takes time, drug repurposing is one of the avenues. Keeping that in mind, we have tried to shed light on some of the drugs, using molecular docking/modeling stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…The review showed Curcumin-derived polyphenols exhibit antiviral activity for influenza, hepatitis C virus, HIV, anti-inflammatory, antibacterial, and antioxidant properties and also exert substantial anticarcinogenic activities (Heger et al, 2013;Nelson et al, 2017;Praditya et al, 2019b). Wet lab experimental approaches for the study of interactions between therapeutic substance and target proteins are not cheap, not safe, labors, and time-consuming (Basak et al, 2020;Bachmann & Lewis, 2005). There are many alternative methods are available for solving these problems.…”
Section: Discussionmentioning
confidence: 99%
“…The review showed Curcumin-derived polyphenols exhibit antiviral activity for influenza, hepatitis C virus, HIV, anti-inflammatory, antibacterial, and antioxidant properties and also exert substantial anticarcinogenic activities (Heger et al, 2013;Nelson et al, 2017;Praditya et al, 2019b). Wet lab experimental approaches for the study of interactions between therapeutic substance and target proteins are not cheap, not safe, labors, and time-consuming (Basak et al, 2020;Bachmann & Lewis, 2005). There are many alternative methods are available for solving these problems.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, CBD was the most potent out of five phyto-cannabinoids (cannabidiol, cannabidiolic acid, delta-9-tetrahydrocannabinol, delta-9-tetrahydrocannabinolic acid, cannabinol), and even more potent than the reference drugs lopinavir, chloroquine and remdesivir. Intriguingly, CBD may be able to bind also to the spike protein as has been demonstrated in a recent in silico study [8]. A further peptide possibly playing more than just one role in early infection is apelin.…”
Section: Preclinical Data Suggest a Potential Benefit Of Cannabidiol mentioning
confidence: 76%
“…It is concluded that grazoprevir could be the most potent inhibitor of spike glycoprotein, as several studies are focusing on the efficiency of blocking spike by glycoprotein (Ibrahim et al, 2020 ; Kadioglu et al, 2020 ; Mohamed et al, 2020 ; Shah et al, 2020 ). Other therapeutics such as ivermectin (Ibrahim et al, 2020 ; Kadioglu et al, 2020 ), ledipasvir, teniposide, velpatasvir (Chen Y. W. et al, 2020 ; Kadioglu et al, 2020 ), and rifabutin (Bank et al, 2020 ; Kadioglu et al, 2020 ) also showed potential inhibitory action against the spike glycoprotein of SARS-CoV-2. Among the suggested candidate drugs of spike protein, 17 drug molecules were repurposed for COVID-19 and approved by the FDA (Home, 2013 ).…”
Section: In Silico Medicinesmentioning
confidence: 99%
“…Isothymol has been suggested against human ACE2 for the treatment of COVID-19, although wet lab investigation is yet to be started (Abdelli et al, 2020 ). Moreover, it has been found that HCQ has the maximum capacity to act on multiple drug targets, namely, Mpro, spike protein, RNA-dependent RNA polymerase, interleukin (IL) 6, IL2, IL10, and interferon alpha 1 (IFNA1) (Bank et al, 2020 ; Elfiky, 2020 ; Kim and Kim, 2020 ; Srivastava et al, 2020 ). Few other drug molecules were found to be effective against multiple drug targets.…”
Section: In Silico Medicinesmentioning
confidence: 99%
See 1 more Smart Citation